Urethral Hairballs as a Long-Term Complication of Hypospadias Repair: Two Case Reports. (8th August 2012) - Kampantais, Spyridon; Dimitriadis, Charalampos; Laskaridis, Leonidas; Perdikis, Ioannis; Kirtsis, Petros; Toutziaris, Chrysovalantis
Abstract : Many times hair-bearing urethral grafts have been used inadvertently in the treatment of hypospadias. This can be accompanied with numerous troublesome long-term complications such as formation of stones, diverticula, and hairballs. We report two cases of men with a history of hypospadias repair being affected by such complications. We also discuss about their management and the effect of thioglycolic acid instillation to stop hair growth in the urethra mucosa in the second case.